Aftermath of COVID-19 in container shipping (environmental sustainability) - Ong, Shi Hui (Nanyang Technological University, 2023)
Increasing sustainability and climate change concerns around the world have shifted consumers’ preferences as well as the progression of the global economy. In addition to maximising profits and minimizing loss, more companies are looking to contribute to the economy sustainably in terms of environmental sustainability, social sustainability, and economic sustainability.